Pendidikan Agama Islam Bagi Anak Usia Dini Di Lingkungan Keluarga - Sari, Nelfa; Hakim, Anwar (Zuriah : Jurnal Pendidikan Anak Usia Dini, 2023)
This research was conducted to analyze Islamic religious education for early childhood in the family environment. This research is a narrative literature review using an overview article. The data analysis technique used is conduct a search, identify keywords, review abstracts and article and document results. The results of this research are Islamic religious education material for early childhood in the family environment, namely faith education, worship education, and moral education. Meanwhile, Islamic religious education methods for early childhood in the family environment are example, advise, customs attention, training, experience, games, songs, stories, praise, punishment, targhib and tarhib.